Section 44 of the English Arbitration Act 1996 and third parties to arbitration. (4th November 2020) - Burn, George; Cheung, Kevin
Abstract: Court-ordered interim measures serve to reinforce and support tribunals' jurisdiction and powers. Practitioners have long understood that national courts can and should apply this supportive jurisdiction against third parties to arbitration over whom most tribunals lack power. However, since 2014, English courts have held, in a series of first instance decisions, that their powers under section 44 of the English Arbitration Act 1996 are not exercisable against third parties to arbitration. Save for one of the powers under section 44, which the Court of Appeal has recently held to be applicable to third parties, this judicial interpretation that section 44 is not applicable to third parties remains in place. The authors argue that this judicial interpretation of section 44 runs contrary to its underlying purpose and the role of the courts in arbitration, and leaves a gap in a regime known for its supportive attitude vis-à-vis arbitration.